کسمانک ءُ بلوچی کسمانک ءِ بنگیج ءُ دیمرئی: Drama: Evolution and development of Balochi Drama - Dashti, Zahid (Hanken, 2009)
The tradition of the Balochi drama exists long before in the traditional games. Folk stories and poetry and other aspects of everyday life but the concept of new drama is earlier. The written history of the Balochi drama starts from 1950s. The aim of this paper is to focus the origin, derivative sources and a comparative study among the other languages like Urdu and English. The progress and evolution of Balochi drama in the Radio and TV, and the stage drama will also be discussed. Financial support of the Government for the Promotion of Balochi drama and its supervision will also be mentioned.